IMF Survey, Volume 33, Issue 06. (IMF Survey; IMF Survey ;, 2004)
David Burton, a U.K. national who has worked at the IMF since 1981, took over as Director of the Asia and Pacific Department in late 2002. Laura Wallace spoke with him about the dramatic changes that are now shaping the region, including the increasing economic prominence of China, deepening regional integration, a bigger emphasis on transparency, and the recent massive buildup of foreign exchange reserves.